Komunikasi Inklusif dalam Mendorong Kolaborasi Keagamaan: Studi Kasus Masjid Syuhada Yogyakarta - Angga Nur Rohman; Syarifudin, Maulana; Eka Nurhalizah, Mevy; Achmad Alimin, Unun (Jurnal Komunikasi Islam, 2025)
This study examines the role of inclusive communication practices at Masjid Syuhada Yogyakarta in fostering inter-organizational religious collaboration amid increasing exclusivity in mosque governance in Indonesia. While many mosques are institutionally affiliated with specific religious organizations or political interests, this study adopts a qualitative case study approach to explore an alternative communicative model. Drawing on Jürgen Habermas’s concepts of the religious public sphere and communicative action, the analysis evaluates how organizational narratives and practices articulate validity claims of truth, appropriateness, and sincerity. Data were collected through in-depth interviews, participant observation, and document analysis. The findings reveal that Masjid Syuhada sustains an inclusive communicative environment by maintaining a non-partisan stance, cultivating dialogical spaces resembling an ideal speech situation, and institutionalizing communicative neutrality across diverse Islamic organizations. This positioning enables the mosque to function as a living religious public sphere that facilitates collaboration beyond ideological boundaries.